2020
DOI: 10.21608/aimj.2020.39083.1305
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Diagnostic Hysteroscopy as a Tool for Diagnosis of Tubal Factor of Infertility in Comparison to Diagnostic Laparoscopy

Abstract: Background: Fallopian tube obstruction is believed to play a role in 12-33% of subfertile couples. Therefore, the patency evaluation of fallopian tubes is a significant part of subfertile couple's work. Aim of the work: This work aims at comparing the sensitivity and specificity of the hysteroscopic assessment of tubal patency by the bubble test to diagnostic laparoscopy and hysterosalpingogram in infertile patients. Patients and Methods: A total of 100 women were recruited to the study during the period betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Hysteroscopy showed an overall accuracy of 91.5% [CI: 85.1%-97%] compared to laparoscopy. Consistent with our findings, Hefny et al [13] also reported a high level of agreement between the two methods of tube detection.…”
Section: Discussionsupporting
confidence: 92%
“…Hysteroscopy showed an overall accuracy of 91.5% [CI: 85.1%-97%] compared to laparoscopy. Consistent with our findings, Hefny et al [13] also reported a high level of agreement between the two methods of tube detection.…”
Section: Discussionsupporting
confidence: 92%
“…Males are reported to be primarily responsible for 20-30% of infertility cases, although they also contribute to 50% of all cases. Secondary infertility is the most prevalent kind of female infertility, which is caused by infections in the reproductive system [3][4][5] . Female infertility represents approximately 65% of the overall causes for infertile couples.…”
Section: Introductionmentioning
confidence: 99%